Awareness and Perception of the Roles and Services of Physiotherapy among Private Healthcare Practitioners in Kota Kinabalu, Sabah - Wong, Lydia; Labao, Hernan Cortez; Yughdtheswari, Muniandy; Clements, Jim Brown (INTI International University, 2020)
Background: Physiotherapy helps restore movement and function when a person is affected by injury, illness, or disability. Due to its non-invasive and cost-effective techniques, Physiotherapy is rapidly gaining popularity among the people however the awareness of Physiotherapy among various health care practitioners is questionable. This study aims to study the current level of awareness and perception of Physiotherapy roles and services among health care practitioners in the private sector working at Kota Kinabalu. Methods: A quantitative, cross-sectional study was adopted with a total of 120 participants with an age range between 20 to 60 years old who were recruited using predefined inclusion and exclusion criteria. A self-developed questionnaire on awareness and perception of the roles of Physiotherapy was distributed to the participants. Results: The data collected revealed all 120 participants have a moderate level of awareness although 64.2 % of participants did not receive any Physiotherapy treatment before. Musculoskeletal Physiotherapy (86.70%), Sports Physiotherapy (86.70%), rehabilitation, and pain management (70%) were the ones that have received the highest awareness. Not only that, but 78.13% of participants also reported having no negative perception of Physiotherapy. Conclusions: There is moderate awareness regarding the level of awareness and positive perception towards the roles and services of Physiotherapy among health care practitioners in the private sector at Kota Kinabalu, Sabah. These indicated that health care practitioners are open to Physiotherapy practices and they are very likely to refer patients to a Physiotherapist when necessary.